THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL MANAGEMENT ON THE PERFORMANCE OF TAILORING SMES IN NORTH TORAJA - Pareang, Triani; Mongan, Benyamin; Halik, Johannes Baptista (Entrepreneurship Undergraduate Program at Amkop Business School, 2025)
This research analyzes the influence of financial literacy and financial management on the performance of tailoring Small and Medium Enterprises (SMEs) in North Toraja. SMEs play a strategic role in the Indonesian economy, but face obstacles in managing finances. The methodology used was descriptive quantitative research using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach on 57 respondents who were active in the sewing sector. The research results show that financial literacy does not have a significant influence on the performance of tailoring SMEs, while financial management is proven to have a significant positive impact. These findings emphasize the importance of good financial management in improving business performance. Although financial literacy still plays an important role, it has not been implemented consistently by SMEs.Keywords: : Financial Literacy; Financial management; SME Performance; SEM-PLS; North Toraja